Enhancement of teaching outcome through neural prediction of the students' knowledge state - Zheng, Lifen; Chen, Chuansheng; Liu, Wenda; Long, Yuhang; Zhao, Hui; Bai, Xialu; Zhang, Zhanjun; Han, Zaizhu; Liu, Li; Guo, Taomei; Chen, Baoguo; Ding, Guosheng; et al. (Human brain mapping, 2018)
The neural mechanism for the dyadic process of teaching is poorly understood. Although theories about teaching have proposed that before any teaching takes place, the teacher will predict the knowledge state of the student(s) to enhance the teaching outcome, this theoretical Prediction‐Transmission hypothesis has not been tested with any neuroimaging studies. Using functional near‐infrared spectroscopy‐based hyperscanning, this study measured brain activities of the teacher–student pairs simultaneously. Results showed that better teaching outcome was associated with higher time‐lagged interpersonal neural synchronization (INS) between right temporal‐parietal junction (TPJ) of the teacher and anterior superior temporal cortex (aSTC) of the student, when the teacher's brain activity preceded that of the student. Moreover, time course analyses suggested that such INS could mark the quality of the teaching outcome at an early stage of the teaching process. These results provided key neural evidence for the Prediction‐Transmission hypothesis about teaching, and suggested that the INS plays an important role in the successful teaching.